SAT0498 MRI Remission In Patients with Rheumatoid Arthritis in Clinical Remission. (23rd January 2014) - Cosso, C.; Barbieri, F.; Zampogna, G.; Paparo, F.; Aleo, E.; Pizzorni, C.; Garlaschi, G.; Cutolo, M.; Cimmino, M. A.
Abstract : Background: Novel treatment strategies of rheumatoid arthritis (RA) allow to reach remission in an increasing number of patients. However, follow-up studies often revealed progressive structural deterioration of the joints in patients in clinical remission. This apparent discordance has been clarified by advanced imaging techniques, such as ultrasonography (US) and magnetic resonance imaging (MRI), which showed persistence of subclinical synovitis in the majority of patients in clinical remission. Objectives: This study is concerned with an evaluation of the frequency of MRI remission in patients with DAS 28 CRP lower than 2.6, according to different MRI measures of disease activity and clinical definitions of remission. Methods: 35 consecutive RA patients (30 women, mean age 53, 2±13, 8 years) affected by RA diagnosed according to the 1987 ACR criteria who were in DAS 28 CRP remission were studied. Demographic data and clinical and laboratory findings necessary for the evaluation of DAS 28 CRP, DAS 28 ESR, SDAI, CDAI, the preliminary criteria by Pinals et al., and the Boolean-based definition of remission suggested by the ACR/EULAR study group, were recorded. MRI of the dominant hand was performed with a 0.2T extremity-dedicated machine (Artoscan C, Esaote, Genoa, Italy) using pre and post contrast T1 weighted turbo 3D and STIR sequences. MRI was analyzed using the OMERACT-RAMRIS score [synovitis, bone oedema (BME), erosions of distal radium and ulna, wrist and metacarpophalangeal joints] and the dynamic contrast-enhanced technique for wrist synovitis (DCE-MRI). The enhancement ratio was calculated both as the rate of early enhancement (REE) and the relative enhancement (RE). Results: Median duration of remission was 5 months (1-62 months). Of the 35 patients in DAS 28 CRP remission, 22 (71%) were also in Pinals et al. criteria remission, 19 (54.3%) were in DAS 28 ESR remission, 17 (48.6%) in SDAI remission, 16 (45.7%) in CDAI remission and 13 (37.1%) in remission according to the recent ACR/EULAR definition. 31/35 patients could complete the post-contrast sequences. The mean RAMRIS score for wrist synovitis was 3.5±1.6 (range 0-8). Four patients (12.9%) showed no detectable synovitis by RAMRIS. By DCE-MRI no synovial membrane enhancement was seen for REE in 8 (25.8%) and for RE in 5 (16.1%) patients. BME was present in 33/35 patients (94.3%) with a median RAMRIS score of 7 (range 0-38). No difference between patients in remission or not according to the different criteria was observed for the RAMRIS synovitis score, REE and RE. The RAMRIS synovitis score and DAS 28 CRP at remission were inversely correlated with its duration (p=0.02 and p=0.01, respectively). Conclusions: Our data suggest that nearly 13% of RA patients in DAS 28 CRP clinical remission do not show any MRI synovitis. This result is in keeping with the literature. Using DCE-MRI, the number of patients who can be considered in remission almost doubled. Follow-up studies are ongoing to evaluate if the clinical outcome will vary according to the different types of clinical and MRI remission. Disclosure of Interest: None Declared